Evaluation of risk factors and clinical presentation of adenoid hypertrophy among children attending the pediatric outpatient department of tertiary care hospital in Dhaka division - Alam, Morshed; Razzak, M. Abdur; Rahman, S. M. Azizur; Islam, Sofiqul; Akter, Shaheen (International Journal of Contemporary Pediatrics, 2022)
Background: Adenoid hypertrophy (AH), also known as enlarged adenoid, refers to the unusual growth of the adenoids. AH and its consequences are common in the entire childhood period. The adenoids are small masses of lymphatic tissue located in the upper airway, between the nose and the back of the throat. Methods: This cross-sectional study was conducted from January 2021 to December 2021 over a period of 12 months. All the children aged 1-18 years attending the pediatric outpatient department (OPD) who had known risk factors or sign-symptoms of AH underwent a lateral nasopharyngeal x-ray to confirm the presence of an enlarged adenoid. Those children who had enlarged adenoids were analyzed in this study. Results: A total of 1289 children aged 1-18 years attended the pediatric OPD over 1 year of the study period, out of them, 118 had evidence of enlarged adenoid on lateral nasopharyngeal x-ray, giving a prevalence of 2.3%. Among the 118 radiologically proved AH cases, 112 (95%) were symptomatic and 6 (5%) were asymptomatic having risk factors only. The peak age of diagnosis of AH in this study was between 12-72 months (43.4%). The mean age of presentation was 100.6±58 months. There was a male predominance with male to female ratio of 1.6:1. AH may be presented without symptoms in 5% of cases or may be presented with complications such as OSA (27%), adenoid facies (14%), and otitis media with effusion with or without hearing impairment (13%). Conclusions: The prevalence of AH among children attending the pediatric outpatient department was 2%, of them 18% had an indication for adenoidectomy. The most common two clinical presentations were mouth breathing and nasal obstruction and the most common complication was obstructive sleep apnea.